PEMANFAATAN MEDIA TIK SIMULASI SEBAGAI KOMPLEMEN EKSPERIMEN PADA PEMBELAJARAN ALAT UKUR - Rizkiyana Rizkiyana; Agus Suyatna; Viyanti Viyanti (Jurnal Pembelajaran Fisika, 2014)
The purposes of this research were to know about the raising of students’ cognitive learning outcomes, to grow of students’ science process skills, to form the characters, to improve activities, and to grow the attitudes of students by using ICT media simulation as complement on experiment of study in measuring instruments. The research has been done in SMPN 1 Tumijajar, Tulang Bawang Barat. This research used the experiment method. The research data were obtained by giving pretest and posttest, and also to observe the students’ Science Process Skills, the students’ characters, the activities, and students’ attitudes. The research conclude that students cognitive raised as 0,4 or medium range, grow the students’ science process skills, form the caracters, improve the activities, and growth the students’ positive attitudes by using ICT media simulation as complement on experiment of study in measuring instruments.Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar ranah kognitif siswa, menumbuhkan KPS, membentuk karakter, mengembangkan aktivitas, menumbuhkan sikap siswa terhadap pemanfaatan media TIK simulasi sebagai komplemen eksperimen pada pembelajaran ukur. Penelitian ini dilaksanakan di SMPN 1 Tumijajar, Tulang Bawang Barat. Penelitian ini menggunakan metode eksperimen. Data penelitian diperoleh dengan cara memberikan pretes dan postes serta observasi terhadap keterampilan proses sains siswa, karakter, aktivitas, dan sikap siswa. Kesimpulan dari penelitian ini adalah terdapat peningkatan rata-rata hasil belajar siswa sebesar 0,4 atau dapat dikategorikan sedang, menumbuhkan keterampilan proses sains siswa, membentuk karakter, mengembangkan aktivitas, dan menumbuhkan sikap positif siswa selama menggunakan media TIK simulasi sebagai komplemen eksperimen pada pembelajaran alat ukur.Kata kunci: aktivitas, karakter, keterampilan proses sains siswa, komplemen eksperimen, media TIK simulasi